Solid pseudopapillary neoplasm of the pancreas with postoperative multiple liver metastases in an older woman: a case report - Lu, Yishan; Huang, Nana; Wang, Ruzhu; Zhang, Yuting; Duan, Haitao; Gao, Ping (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Solid pseudopapillary neoplasm of the pancreas (SPN), also known as Frantz’s tumor is a peculiar pancreatic neoplasm with an unclear pathogenesis. Early surgery often results in a curative effect; however, rare postoperative metastasis can occur. Currently, no standard systemic treatment strategy has been established for metastatic SPN. In this article, we report an older woman with SPN who developed postoperative multiple liver metastases and experienced rapid progression despite sequential systemic therapies.Case Description: A 68-year-old woman who underwent surgical resection of a SPN (approximately 44 months earlier) presented with multiple liver lesions despite having no obvious clinical findings. After laparoscopic distal pancreatectomy and splenectomy, multiple postoperative liver metastases were diagnosed by ultrasound-guided percutaneous liver biopsy, and a CTNNB1 gene mutation was detected. The patient received sequential palliative systemic therapies, however, the disease continued to progress, and she ultimately died 8 months later.Conclusions: SPN is an extremely rare tumor with a relatively good prognosis. Complete surgical resection remains the mainstay of treatment; however, evidence for systemic therapy in unresectable or metastatic SPN remains limited. We report the case of a SPN patient with rare postoperative metastases and a poor prognosis, and describe the treatment course and systemic therapeutic strategy, which may serve as a reference for the management of similar cases.